Inside the hiring process: how managers assess employability based on grit, the big five, and other factors. (14th August 2019) - Butz, Nikolaus T.; Stratton, Reed; Trzebiatowski, Max E.; Hillery, Tyler P.
Hiring managers' priorities are shifting from traditional criteria such as work experience and education to intrinsic traits such as grit and the big five. The purpose of this study was to investigate how hiring managers assess job seeker employability based on grit, the big five, and other factors. Participants were 100 employers from a three-county area in the Midwest USA. The results indicated that service organisations and goods-focused organisations value grit as a hiring criterion above a point of theoretical indifference. Furthermore, several bivariate relationships were found between grit and the big five. Independent samples t -tests revealed that service companies prioritise conscientiousness more than good-focused organisations. Regression analysis showed that 27% of the variability in grit was explained by other hiring criteria. Implications and theoretical contributions are provided for universities, hiring managers, and jobseekers. Specific recommendations include embracing failure, adopting behavioural-based interviewing practices, and conveying grit in application materials.